Every Saint Has A Past, Every Sinner Has A Future: Husnudzon, Belief in A Punitive God, and Belief in Klitih Offender Redeemability - Maria Gracia Amara Pawitra; Luluk Nadiyatun Nadziroh; Malvin Geoffrey Cristianto (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2024)
Ideally, offenders need to gain public belief in their redeemability, which eases their reintegration process and prevents repeated criminal offenses, especially juvenile offenders, as the majority of Klitih offenders are. Otherwise, the fact is that not only do they have to face criminal punishment but also social sanctions, even though they have completed their sentences. This cross-sectional study aimed to examine the role of Husnudzon and belief in a punitive God in determining belief in klitih offender redeemability. The data was collected using Husnudzon Scale, Belief in A Punitive God Scale, and Offender Redeemability scale. The sample was selected using purposive sampling with inclusion criteria, namely, being an Indonesian citizens aged 18–60 years, being a Muslim, living in Special Region of Yogyakarta (DIY) at least since 2016 for at least 2 years, and having updated the news and/or discussed klitih cases in DIY. The results of multiple linear regression analysis (N = 136) showed that Husnudzon positively predicted belief in offender redeemability, and belief in a punitive God negatively predicted belief in offender redeemability. This research suggested that the public should balance two perspectives of religious belief, which are forgiveness-based and punishment-based, to advocate belief in offender redeemability in supporting positive criminal justice.